교통 빅데이터를 활용한 어린이 보호구역 관리지표 개발 - 이상인 (The Graduate School, Ajou University, 2024)
어린이 보호구역은 1995년 어린이 보호구역에 대한 규칙이 제정되고 2003년 개선 사업이 실시된 이래 현재까지 어린이들의 안전을 위해 지속적 인 투입과 관리가 이루어졌다. 2011년 1월에 “도로교통법”과 “어린이보호구역의 지정 및 관리에 관한 특 례법”을 개정하면서 지정 주체가 경찰에서 해당 지자체(시·도 및 구·군)로 바뀌었으며 국고보조사업으로 사업이 추진되고 있다. 최근에는 민식이법이 시행됨에 따라 어린이 보호구역 내 안전시설 설치를 의무화하고 법적인 제 재를 마련하여 어린이의 생명과 안전을 지키기 위해 최선을 다하고 있다. 어린이 보호구역에 대한 지속적인 관심과 투자가 이루어지고 있지만 적절 한 관리가 되지 못하고 있다. 현장 상황을 반영한 자료가 아닌 과거 사고 데이터에 근거하여 사업을 추진하고 있기에 현장과 괴리감이 발생한다. 이 에 이번 연구에서는 현장 데이터와 기존 자료를 융합하여 관리 지표를 작 성하였다. 정량적 데이터는 교차로 통과교통량, 중차량 대수, 사고건수를 수집하였으 며 정성적 데이터로 학생수, 시설물 유형, 통학로 주변환경, 안전시설 설치 유무를 분석하였다. 통계적 검증을 거쳐 사고건수에 영향을 주는 변수에 대 해 분석하였으며 사고건수와 통과교통량은 양의 상관관계, 사고건수와 중차 량 대수는 음의 상관관계가 나타났다. 통과교통량과 중차량 대수를 기반으로 예상사고건수를 추정하고 정성적 데이터는 각각 지표마다 등급화하여 위험도 점수를 매겼으며 실제 인천시 어린이 보호구역에 적용해보았다. 향후 어린이 보호구역 개선사업 추진시 예상사고건수와 위험도 점수를 매겨서 구역마다 적정성을 따져본다면 더욱 효과적으로 어린이 보호구역을 관리할 수 있을 것이다.|Children's protection zones have been continuously introduced and managed for the safety of children since the rules on children's protection zones were enacted in 1995 and the improvement project was implemented in 2003._x000D_ In January 2011, the "Road Traffic Act" and the "Special Act on the Designation and Management of Children's Protection Zones" were revised, and the designated entity was changed from the police to the relevant local government (city, province, district, and county), and the project is being promoted as a state-funded project. Recently, with the enforcement of the Civil Service Act, it is doing its best to protect the life and safety of children by mandating the installation of safety facilities in children's protection zones and preparing legal sanctions._x000D_ Although there is continuous interest and investment in child protection zones, it has not been properly managed. Since the project is being promoted based on past accident data, not data reflecting the field situation, a sense of separation from the field occurs. Therefore, in this study, a management index was prepared by fusion of field data and existing data._x000D_ Quantitative data collected traffic through intersections, the number of heavy vehicles, and the number of accidents, and analyzed the number of students, types of facilities, the environment around the school road, and the installation of safety facilities as qualitative data. Through statistical verification, an equation was calculated for the variable affecting the number of accidents, and there was a positive correlation between the passing traffic volume and the number of heavy vehicles._x000D_ Based on the traffic volume and the number of heavy vehicles, the estimated number of accidents was estimated, and the qualitative data was graded by each indicator to score the risk, and it was actually applied to the Incheon Children's Protection Zone. In the future, if the number of accidents and risk scores are scored to determine the appropriateness of each individual area, it will be possible to manage the child protection zone more effectively.
학위논문(석사)--교통ITS학과,2024. 2
Keywords: Big data; ITS; Transportation; school zone; traffic; 관리지표; 교통; 교통빅데이터; 스마트교차로; 스쿨존; 어린이 교통사고; 어린이보호구역